Pogostemon cablin essential oil affects anxiety- and depressive-like behaviors and the gut microbiota in chronic unpredictable mild stress model rats - Ouyang, Puyue; Kang, Dali; You, Weijing; Shen, Xiaozhong; Mo, Xiaolu; Liu, Yao (Frontiers in Nutrition, 2024)
The gut microbiota is thought to be an important factor that influences brain processes and behaviours through the gut-brain axis. Pogostemon cablin is used in traditional Chinese medicine (TCM) to treat gastrointestinal symptoms. Patchouli essential oil (PCO), the main active agent in P. cablin, is used in aromatherapy for stress relief.The aim of our study was to investigate the effects of orally administered PCO on anxiety-and depressive-like behaviours and the gut microbiota. We constructed a rat model of chronic unpredictable mild stress (CUMS) and explored the anxiolytic-and antidepressant-like effects of PCO using the open field test (OFT) and forced swim test (FST). Changes in the abundance of the gut microbiota, short-chain fatty acids (SCFAs), and other related molecules were assessed to determine the role of the gut microbiota. Our results showed that CUMS induced an anxiety-like phenotype in the OFT, which was reversed by PCO, and that PCO also significantly mitigated the depression-like behaviours caused by CUMS in the FST. Furthermore, we found that PCO increased the relative abundances of several probiotics, including Bacteroides and Blautia, and decreased the relative abundances of Ruminococcus_1 and Ruminococcus_2, which were increased by CUMS. Regarding SCFAs, the metabolites of the gut microbiota, PCO increased the concentration of propionic acid and decreased that of caproic acid. Finally, PCO restored the serotonin (5hydroxytryptamine, 5-HT) level in the hippocampus, which had been decreased by CUMS. The results of this study suggested that PCO can improve stress-related anxiety-and depression-like behaviours and might exert its effects on the central nervous system through interactions with the gut microbiota.